ISLAMIC LEADERSHIP FOR SUSTAINABILITY: A SYSTEMATIC LITERATURE REVIEW USING PRISMA - Abdul Razak, Arbaiah; Mhd. Sarif, Suhaimi; Ismail, Yusof (Online Journal of Islamic Management and Finance (OJIMF), 2022)
This paper presents a systematic literature review on Islamic leadership for sustainability with the aim to survey the state of knowledge on the topic. The paper reviews the scope of Islamic leadership initiatives for sustainable development in a variety of contexts. The study employed the Preferred Reporting Items for Systematic Reviews (PRISMA) method as a guideline for systematic data collection. Data was surveyed from journal articles over two decades, i.e., between 2000 and 2021. The analysis included a total of 63 articles from the EBSCO Discovery Service (EDS) database. Results show that the frequency of publications on Islamic leadership for sustainable development was increasing for the past ten years, led by Muslim countries. This study also shows that Islamic leadership and conventional leadership styles share many values. The tawhidic paradigm emerges as a distinguishing feature of Islamic leadership. Findings indicate that Islamic leadership is geared towards comprehensive efforts for social sustainability, at individual, organizational and national levels.